Dampened ventilatory response to added dead space in newborns of smoking mothers. Issue 4 (5th May 2005) - Bhat, R Y; Broughton, S; Khetriwal, B; Rafferty, G F; Hannam, S; Milner, A D; Greenough, A
Abstract : Background: Term newborns can compensate fully for an imposed dead space (tube breathing) by increasing their minute ventilation. Objective: To test the hypothesis that infants of smoking mothers would have an impaired response to tube breathing. Design: Prospective study. Setting: Perinatal service. Patients: Fourteen infants of smoking and 24 infants of non-smoking mothers (median postnatal age 37 (11–85) hours and 26 (10–120) hours respectively) were studied. Interventions: Breath by breath minute volume was measured at baseline and when a dead space of 4.4 ml/kg was incorporated into the breathing circuit. Main outcome measures: The maximum minute ventilation during tube breathing was determined and the time constant of the response calculated. Results: The time constant of the infants of smoking mothers was longer than that of the infants of non-smoking mothers (median (range) 37.3 (22.2–70.2) v 26.2 (13.8–51.0) seconds, p = 0.016). Regression analysis showed that maternal smoking status was related to the time constant independently of birth weight, gestational or postnatal age, or sex (p = 0.018). Conclusions: Intrauterine exposure to smoking is associated with a dampened response to tube breathing.